Potential Mechanisms underlying the Protective Effect of Pregnancy against Breast Cancer: A Focus on the IGF Pathway - Katz, Tiffany A. (Frontiers in Oncology, 2016)
A first full term birth at an early age protects women against breast cancer by reducing lifetime risk by up to 50%. The underlying mechanism resulting in this protective effect remains unclear, but many avenues have been investigated, including lobular differentiation, cell fate, and stromal composition. A single pregnancy at an early age protects women for 30-40 years and this long-term protection is likely regulated by a relatively stable yet still modifiable method, such as epigenetic reprogramming. Long lasting epigenetic modifications have been shown to be induced by pregnancy and to target the IGF pathway. Understanding how an early first full term pregnancy protects against breast cancer and the role of epigenetic reprogramming of the IGF system may aid in developing new preventative strategies for young healthy women in the future.